Fractional Order Difference Equations - J. Jagan Mohan; G. V. S. R. Deekshitulu (International Journal of Differential Equations)
A difference equation is a relation between the differences of a function at one or more general values of the independent variable. These equations usually describe the evolution of certain phenomena over the course of time. The present paper deals with the existence and uniqueness of solutions of fractional difference equations.